Asian American and Pacific Islander children and mental health - Leon, Frederick T. L. (Child psychology and mental health., 2011)
There are some three million Asian American children under age 18 living in the United States today. Hailing from 29 subgroups that differ in language, religion, and customs, they can be one of the most challenging groups to research and understand. What factors put these children at risk? Conversely, what fuels those who persist and succeed?